1982
DOI: 10.1136/vr.111.6.122
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of embryos from bovine leukaemia virus-infected cattle to uninfected recipients: preliminary results

Abstract: One hundred and fifty-one, day 6 or 7, embryos collected from cattle infected with bovine leukaemia virus (BLV) were transferred to uninfected recipients. Thirty-two pregnancies resulted. Two animals aborted at seven months. Three sets of twins and one single calf were still-born. The remaining 26 pregnancies produced 27 live calves which were raised to six months of age. All of the recipients, pregnant and non-pregnant, and all of the calves remained serologically negative for antibodies to BLV-glycoprotein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Embryo transfer from infected dams to seronegative recipients can be an effective means to control BLV transmission in such a situation. [127][128][129][130] A slow but more economically viable alternative is the implementation of a two herd scheme, by which BLV-infected animals are maintained on the farm, but managed separately, with separate equipment or adequate disinfection of utensils. It requires the routine identification of new infections in the BLV-negative herd, and their transfer to the BLV-positive herd.…”
Section: Traditional Blv Control Approachmentioning
confidence: 99%
“…Embryo transfer from infected dams to seronegative recipients can be an effective means to control BLV transmission in such a situation. [127][128][129][130] A slow but more economically viable alternative is the implementation of a two herd scheme, by which BLV-infected animals are maintained on the farm, but managed separately, with separate equipment or adequate disinfection of utensils. It requires the routine identification of new infections in the BLV-negative herd, and their transfer to the BLV-positive herd.…”
Section: Traditional Blv Control Approachmentioning
confidence: 99%
“…Among the lists of infectious agents, bovine leukaemia virus (BLV) has been documented not to be associated with, or to be transmitted by, embryos collected in vivo from seropositive donors (Eaglesome and others 1982, Hare and others 1985). However, no information regarding the interaction of BLV with in vitro produced embryos exists.…”
mentioning
confidence: 99%
“…IT HAS been shown that the intact zona pellucida (ZP) of bovine embryos fertilised in vivo and in vitro is an effective barrier against many pathogenic agents (Bielanski 1997, Wrathall and Sutmoller 1998). Among the lists of infectious agents, bovine leukaemia virus (BLV) has been documented not to be associated with, or to be transmitted by, embryos collected in vivo from seropositive donors (Eaglesome and others 1982, Hare and others 1985). However, no information regarding the interaction of BLV with in vitro produced embryos exists.…”
mentioning
confidence: 99%
“…In cattle, the Foot-and-mouth virus [40,41,49], Bluetongue virus [23,56], brucellosis [3,25,51,52], tuberculosis [18] and enzootic bovine leukosis [26] do not seem to represent any risk of transmission by ET. On the contrary, the risks associated with Mycobacterium paratuberculosis, the Bovine herpes virus-1 and non conventional agents such as prions are more questionable.…”
Section: In Vivo Produced Embryosmentioning
confidence: 99%